2019
DOI: 10.1175/jas-d-18-0279.1
|View full text |Cite
|
Sign up to set email alerts
|

Vertical Structure and Microphysical Characteristics of Frontal Systems Passing over a Three-Dimensional Coastal Mountain Range

Abstract: As midlatitude cyclones pass over a coastal mountain range, the processes producing their clouds and precipitation are modified, leading to considerable spatial variability in precipitation amount and composition. Statistical diagrams of airborne precipitation radar transects, surface precipitation measurements, and particle size distributions are examined from nine cases observed during the Olympic Mountains Experiment (OLYMPEX). Although the pattern of windward enhancement and leeside diminishment of precipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 59 publications
1
23
0
Order By: Relevance
“…feature is further demonstrated in transects of Figure 3C, and could be a response of greater orographic enhancement of precipitation on the first rise of the strong, cross-barrier moisture flux from ARs as has been suggested by other studies on the coastal western mountains of North America (Neiman et al, 2017;Zagrodnik et al, 2018Zagrodnik et al, , 2019. Figure 3 illustrates the strong orographic effects of the Andes on the snow accumulation and the ARs contribution to this accumulation in along-and cross-barrier directions.…”
Section: Ars Contribution To Snowpackssupporting
confidence: 72%
“…feature is further demonstrated in transects of Figure 3C, and could be a response of greater orographic enhancement of precipitation on the first rise of the strong, cross-barrier moisture flux from ARs as has been suggested by other studies on the coastal western mountains of North America (Neiman et al, 2017;Zagrodnik et al, 2018Zagrodnik et al, , 2019. Figure 3 illustrates the strong orographic effects of the Andes on the snow accumulation and the ARs contribution to this accumulation in along-and cross-barrier directions.…”
Section: Ars Contribution To Snowpackssupporting
confidence: 72%
“…Each CFAD was normalized by its overall maximum at a horizontal interval of 1 dBZ and a vertical interval of 0.25 km. Compared with normalization by level maximums (McMurdie et al, 2018), this method is more suitable for comparing results at different heights (Zagrodnik et al, 2019; Zhang et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…The broader distribution and relatively higher median value of D m represent the continental convection on the mountain's leeward side. Zagrodnik et al (2019) also observed the narrow D m distribution during the Olympic Mountains Experiment (OLYM-PEX) on the Olympic peninsula's windward side.…”
Section: Dsd Overview -Topographic Perspectivementioning
confidence: 87%